Valorization of Coffee Waste through Zeolite-based Membrane Development for Peat Water Treatment - Aldian, Dwinka; Aditama, Pradhipta; Rizky, Ahmad; Noviana, Siska; Natalia, Debora (Journal of Innovation Process and Environmental Technology, 2025)
The availability of clean, consumable water is a fundamental aspect of life. Peat water, commonly found in peatlands and lowland areas, is characterized by high levels of dissolved organic matter, a brownish color, and significant acidity. This study develops a membrane-based filtration system utilizing a combination of coffee grounds and zeolite as the main materials to improve peat water quality. The research involves hydrothermal processing, membrane calibration, and filtration performance evaluation. The study was conducted using three variations in the composition of coffee grounds and zeolite to optimize filtration effectiveness. The analysis results revealed variations in the characteristics of the filtered water based on the membrane composition used. For a 50:50 coffee grounds-to-zeolite ratio, the measured parameters included a pH of 5, TDS of 60 mg/L, turbidity of 16.12 NTU, and electrical conductivity of 156 µS/cm. The 70:30 composition has a pH of 6, TDS of 79 mg/L, turbidity of 12.45 NTU, and electrical conductivity of 158 µS/cm. Meanwhile, the 90:10 composition resulted in a pH of 6, TDS of 62 mg/L, turbidity of 16.48 NTU, and electrical conductivity of 160 µS/cm. A comprehensive evaluation indicated that variations in membrane composition significantly influenced filtration effectiveness, as reflected in changes to water quality parameters such as pH, Total Dissolved Solids (TDS), and turbidity.